Assessing the wear properties of plasma electrolytic oxidation TiO2 coatings incorporated ZrO2 nanoparticles on Cp-Ti in simulated body fluid - Maryam Molaei; Arash Fattah-alhosseini; Meisam Nouri; Mosab Kaseem (Applied Surface Science Advances, 2024)
TiO2 oxide coatings incorporated ZrO2 nanoparticles were prepared on Cp-Ti using the plasma electrolytic oxidation (PEO) process in electrolyte solutions containing dispersed ZrO2 nanoparticles. The coatings’ microstructure, roughness, and composition were characterized using scanning electron microscopy (SEM), roughness profilometry, and X-ray diffractometry (XRD) analyses, respectively. The coatings’ friction and wear characteristics were examined using a ball-on-disk sliding test in a simulated body fluid (SBF) electrolyte. The as-prepared oxide coatings had a rough and porous surface structure, primarily consisting of rutile and/or anatase TiO2, tetragonal ZrO2, and ZrTiO4. ZrO2 nanoparticles were incorporated into the TiO2 coating layers and were found on the surface or in the pores. The wear and friction behavior of the oxide coatings were influenced by the quantity of ZrO2 nanoparticles (1 g/L, 3 g/L, and 5 g/L) in the electrolyte solution. The wear resistance of coatings improved by decreasing the wear rate by about 8 % (from 2.31 × 10−6 mm3/Nm to 2.11 × 10−6 mm3/Nm) when the ZrO2 nanoparticles concentration in the electrolyte solution rose from 1 g/L to 5 g/L, because of the formation of more of harder ZrO2 and ZrTiO4 phases in the coatings.